1992
DOI: 10.1128/aem.58.12.4042-4044.1992
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Selenate and Selenite to Elemental Selenium by a Pseudomonas stutzeri Isolate

Abstract: Pseudomonas stutzeri isolate rapidly reduced both selenite and selenate ions to elemental selenium at initial concentrations of both anions of up to 48.1 mM. Optimal selenium reduction occurred under aerobic conditions between pH 7.0 and 9.0 and at temperatures of 25 to 35°C. Reduction of both selenite and selenate was unaffected by a number of anions except for sulfite, chromate, and tungstate ions, which inhibited both growth and reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(99 citation statements)
references
References 13 publications
4
95
0
Order By: Relevance
“…Because S. maltophilia is incapable of using either SeO 4 2or SeO 3 2as a terminal electron acceptor during anaerobic growth (data not shown), the reduction of both Se oxyanions may be a mechanism of resistance. Lortie et al (1992) reported that the aerobic reduction of SeO 4 2and SeO 3 2to Se∞ by a Pseudomonas stutzeri isolate functioned as a detoxification mechanism as there was no evidence of dissimilatory Se reduction. In S. maltophilia a detoxification mechanism may be responsible, but it appears unlikely as the formation of Se∞ occurs during stationary phase and not during exponential growth.…”
Section: Reduction Of Selenate and Selenitementioning
confidence: 99%
“…Because S. maltophilia is incapable of using either SeO 4 2or SeO 3 2as a terminal electron acceptor during anaerobic growth (data not shown), the reduction of both Se oxyanions may be a mechanism of resistance. Lortie et al (1992) reported that the aerobic reduction of SeO 4 2and SeO 3 2to Se∞ by a Pseudomonas stutzeri isolate functioned as a detoxification mechanism as there was no evidence of dissimilatory Se reduction. In S. maltophilia a detoxification mechanism may be responsible, but it appears unlikely as the formation of Se∞ occurs during stationary phase and not during exponential growth.…”
Section: Reduction Of Selenate and Selenitementioning
confidence: 99%
“…Redox poise is maintained through the removal of excess electrons via a membrane-bound, FADH 2 -dependent metal reductase (MORase). Wolinella succinogenes [64], Desulfovibrio desulfuricans [65], speci¢c strains of Pseudomonas stutzeri [66] and E. cloacae [67] are capable of reducing sub-millimolar levels of Se(VI) to Se(0). This activity could be attributed to other reductases that have a broad range substrate speci¢city.…”
Section: Toxicitymentioning
confidence: 99%
“…Recently, some bacterial strains which can effectively reduce selenate into selenite or elemental selenium have been reported [2,[6][7][8]12]. They are all gram-negative bacteria.…”
Section: Flavobacterium Okeanokoites Saccharococcus Thermophilus Macrmentioning
confidence: 99%